Binalebu-2: a high yielding, year-round, scented and seedless variety of lemon - Tasmin, S; Islam, MR; Alam, MS; Mehedi, MNH (Bangladesh Journal of Nuclear Agriculture, 2023)
Citrus fruits, especially Lemon (Citrus limon) belonging to the family Rutaceae are the most important nutritional fruits in Bangladesh. Twenty local and exotic lemon germplasm were collected from home and abroad. The germplasm CL-1 and CL-2 were collected from Darziling, India. The germplasm was evaluated during 2016-17, 2017-18 and 2018-19 at Mymensingh and Tangail and the experiments were carried out following randomized complete design with three replications. Binalebu-1 was used as a check variety in the experiments. Data were recorded on plant height, number of fruits per plant, fruit length, fruit breadth, individual fruit weight, fruit yield per plant, vitamin C and juice contents, and seeds per fruit were recorded. Moreover, reactions to major diseases and insect-pests infestation were also recorded. From the results it was observed that CL-1 was found to be superior to other exotic genotypes and to check variety Binalebu-1. During 2016-17, 2017-18 & 2018-19 at Mymensingh, the highest fruit yield plant-1 (25.45, 32.11 and 40.36 kg), vitamin C (30.11, 29.78 and 29.65 mg 100 g-1), plant height (162.55, 22.41 and 265.23 cm), fruit length (7.72, 7.51 and 7.50 cm), number of fruits plant-1 (172.3, 221.1 and 281.77), juice content fruit-1 (55.25%, 54.11% and 54.31%) and the lowest number of seeds fruit-1 (4, 4 and 4.1) was recorded from CL-1 in all the three consecutive year trials. Similarly at Tangail the highest fruit yield plant-1 (24.94, 31.36, and 35.41 kg), vitamin C (28.44, 30.12 and 30.15 mg 100 g-1), plant height (160.2, 220.9 and 260.54 cm), fruit length (7.66, 7.56 and 7.48 cm), number of fruits plant-1 (170, 223 and 261), juice content fruit-1 (52%, 52% and 53%) and lowest number of seeds fruit-1 (4.1, 4.6 and 5) was recorded from CL-1, which was the highest compared to CL-2 and Binalebu-1 at both locations. The lowest fruit yield plant-1 and vitamin C, highest number of seeds fruit-1 observed at CL-2 at both of Mymensingh and Tangail. Considering the better performance of fruit yield, vitamin C content, juice content and less number of seeds compare to CL-2 and Binalebu-1, CL-1 genotype was selected as a new variety naming Binalebu-2 to grow commercially all over Bangladesh. Bangladesh J. Nuclear Agric, 37(1): 23-30, 2023